Pengaruh Penggunaan Aplikasi Photomath terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Syari, Cahyan; Afri, Lisa Dwi (Jurnal Pendidikan Matematika : Judika Education, 2025)
This research aims to find out whether there is an influence and how the ability to use the photomath application has on students' mathematical problem solving abilities. This research is a quantitative research carried out at DWI SATYA Middle School with a pretest-posttest only one group design. The sample for this research was taken using a total sampling method of 15 students. This research instrument is a test of problem solving abilities in the form of a pretest and posttest. Furthermore, this research data was analyzed using a paired sample t-test after analyzing descriptive statistics and inferential statistics, namely the normality test and homogeneity test. The research results showed that the average pretest score for students who studied using the Photomath application was 36 and the posttest was 66 from the ideal score of 75. There was an increase of 30, which means there was an influence of using the Photomath application on students' mathematics learning with an N Gain score of 0.78 in the high category. Simultaneously, there is a significant influence of learning using the photomath application on students' mathematical problem solving abilities where a sig value of 0.000 is obtained which is smaller than the significance level of 0.05. Keywords: Photomath Application, Mathematical Problem Solving Ability